2021
DOI: 10.1108/cg-09-2020-0389
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility actions and organizational legitimacy at the peak of COVID-19: a sentiment analysis

Abstract: Purpose This paper aims to analyse stakeholder sentiment about the corporate social responsibility (CSR) actions implemented by Italian companies between February 20, 2020 and April 20, 2020, which was the first peak in the outbreak of the COVID-19 health emergency in Italy. Design/methodology/approach Using sentiment analysis, the impact of COVID-19 on CSR actions is analysed through reactions to the news published on Twitter by a sample of Italian news agencies. Findings The analysis indicates that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 78 publications
3
50
0
Order By: Relevance
“…Furthermore, this study shows that CSR, both to primary and secondary stakeholders has a positive and significant effect on improving QSR. QSR also has a positive and significant effect on the sustainability of the company's business performance, which is supported by previous research [29][30] [28]. Therefore, the hypotheses H3, H4, and H5 accepted and concluded that CSR has an indirect effect on the company's business sustainability as research has also shown by previous research [1].…”
Section: Path Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, this study shows that CSR, both to primary and secondary stakeholders has a positive and significant effect on improving QSR. QSR also has a positive and significant effect on the sustainability of the company's business performance, which is supported by previous research [29][30] [28]. Therefore, the hypotheses H3, H4, and H5 accepted and concluded that CSR has an indirect effect on the company's business sustainability as research has also shown by previous research [1].…”
Section: Path Analysissupporting
confidence: 78%
“…Likewise, the quality of the company's relationship with stakeholders is a reciprocal relationship that will provide competitive advantage and company sustainability [28]. The quality of stakeholder relations is affected by the quality of communication, positive company interactions, and trust-building of stakeholders to the company [29]. Companies that continuously build communication and gain the trust from stakeholders through CSR have a positive and significant effect on reducing the company's risk when experiencing environmental disturbances or facing a crisis [28] [30].…”
Section: Quality Of Stakeholder Relations (Qsr)mentioning
confidence: 99%
“…The results indicate that a higher level of perceived brand ethicality motivates customers in the hospitality industry to build brand legitimacy. Customers consider COVID-19 preventive measures as ways to define a brand that acts ethically, and therefore, ethical practices could have several benefits for customers [ 22 ]. During the COVID-19 pandemic, perceived ethical practices could offer several benefits, including avoiding severe acute health effects, including death.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical studies show that the growing interest among scholars in examining how customers grant legitimacy to business firms and their brands is due to the business climate, which includes characteristics such as cynicism, boycotts, ethical purchase, and ethical consumption [ 30 , 55 ]. Recent studies have revealed the need to examine how customers can grant legitimacy to business organizations during pandemic situations such as COVID-19 [ 22 , 47 ]. It is widely accepted that business organizations could demonstrate their accountability and responsibility for social welfare or well-being during pandemics to build social acceptance [ 4 , 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates the effect of CSR and corporate legitimacy during the COVID-19 pandemic. CSR disclosure is effective in supporting a firm's reputation and image in time of crisis, which, in turn, mitigates the impact of the event on the firm's performance (Giacomini et al, 2021).…”
Section: Table 6 Correlation Matrixmentioning
confidence: 99%